Theriogenology - Payan Carreira, Rita (IntechOpen, 2017)
Theriogenology, the field that studies animal reproductive health and disease, is a challenging field that shows a steady growth. It covers diverse aspects of reproduction in domestic and wild animals, including the assisted reproductive techniques, which have enormously enhanced the ability to rescue endangered species and provide a strong support to the high reproductive efficiency requested by livestock production. Reproductive success, as well as infertility, is the culmination of complex physiological and adaptive processes that guarantee, at the end, a species' ability to reproduce and its survival in a challenging and ever-changing environment. In this book, we present to you a collection of manuscripts exploring various aspects of the reproductive function of mammal and marine species. I hope you find this a useful book in your collection.